Family Unification, Siblings, and Skills - Harriet Orcutt Duleep; Mark Regets (Global Labor Organization (GLO), 2018)
Recently proposed immigration reforms would constitute a major break in the 40-year-old U.S. admissions policy favoring family members. Although emphasizing the importance of the nuclear family, the U.S. Commission on Immigration Reform and a house subcommittee on immigration recommend eliminating immigration preferences to other close relatives, including the brothers, sisters, and adult children of U.S. citizens. Under the proposed system, those relatives could not obtain U.S. visas unless they qualified because of specific job skills. Using Immigration and Naturalization Service (INS) data on admissions criteria matched to 1990 Census data, we examine the effect of family admissions on immigrant education, self-employment, and earnings. Of particular relevance to the current debate, we also examine the effect of one of the family-based admission categories recommended for elimination – the preference category that admits the siblings of U.S. citizens. We find that family-based immigrants, in general, have low initial earnings but high earnings growth relative to immigrants admitted on the basis of occupational skills. The earnings growth of immigrants is particularly high in cohorts with relatively high sibling admissions. Furthermore, sibling admissions are positively associated with immigrant self-employment. We also find that immigrant education levels are positively associated with sibling admissions and that the flows of occupation-based immigrants and immigrants admitted under the sibling category are intimately connected, particularly for immigrants from regions of the world where economic opportunities are limited for highly educated individuals. The results on earnings growth, self-employment, and education suggest that eliminating the sibling category may be counterproductive. More generally, the paper adds to our basic knowledge about the complex interactions of admission categories, human capital investment, and earnings growth.
Keywords: J15; J24; J61; K37; 330; immigrant economic assimilation; human capital investment; country of origin; immigrant earnings convergence; immigration law